Amorphous carbon material as well as preparation method and application thereof
By introducing sulfur, selenium or tellurium into the amorphous carbon material to form a crosslinked structure and a turbulent carbon layer, the problem of graphitization of sodium-ion battery carbon-based anode material at high temperature is solved, the sodium storage performance and battery performance are improved, and amorphous carbon materials with high platform capacity and high reversible specific capacity are achieved.
Patent Information
- Application Number
- CN202411371523.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The carbon-based anode materials of existing sodium ion batteries are easily graphitized at high temperatures, resulting in poor sodium storage performance and difficulty in preparing carbon materials with high platform characteristics at lower temperatures.
By introducing sulfur, selenium or tellurium into the amorphous carbon material, a covalent bond of C-MX-C and C-MOX-C are formed, cross-linked structures and turbulent carbon layers are constructed, electron conduction capacity and sodium ion storage performance are improved, and layer spacing and disorder of the material are optimized by regulating the microstructure of the material and the mass percentage content of M elements.
It significantly improves the first Coulomb efficiency and cycling performance of sodium ion batteries, and realizes amorphous carbon materials with high platform capacity and high reversible specific capacity, which are suitable for promotion and application.
Smart Images

Figure CN119650612A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of sodium ion batteries, and specifically relates to an amorphous carbon material and a preparation method and application thereof. Background Art
[0002] Sodium and lithium belong to the same family of alkali metal elements and have similar physical and chemical properties. In addition, the reserves of sodium and its compounds are relatively abundant, making sodium-ion batteries compatible and complementary with lithium-ion batteries in the field of energy storage. Amorphous carbon materials have become a very promising negative electrode material for sodium-ion batteries due to their advantages such as high specific capacity, low sodium storage potential, and good cycle stability. Therefore, the development of low-cost, high-performance carbon-based negative electrode materials is crucial to promote the development of sodium-ion batteries.
[0003] The electrochemical curves of most carbon-based negative electrode materials include a platform segment (the platform segment refers to a section of the electrochemical curve where the slope of the curve is almost 0, usually between 0 and 0.1V) and a slope segment (the slope segment refers to a section of the electrochemical curve where the slope of the curve is non-zero, usually above 0.1V). The low potential characteristics of the platform segment are conducive to the improvement of the output voltage of the whole battery, so the development of carbon materials with high platform capacity has become a hot topic in current research. Summary of the invention
[0004] In view of this, the present application provides an amorphous carbon material and a preparation method and application thereof. By regulating the element doping and microstructure of the amorphous carbon material, its electronic conductivity and sodium storage performance can be improved, and the first coulombic efficiency and cycle performance of the sodium ion battery can be improved.
[0005] In a first aspect, the present application provides an amorphous carbon material, including an M element, wherein the M element is selected from at least one of sulfur, selenium, or tellurium; the amorphous carbon material contains CM X -C covalent bond and C-MO X -C covalent bond, wherein x is selected from 1 or 2; the interplanar spacing d of the amorphous carbon material 002 The amorphous carbon material of the present invention is modified by doping with at least one of sulfur, selenium and tellurium to generate CM in the amorphous carbon material. X -C covalent bond and C-MO X -C covalent bonds form a cross-linked structure, which provides capacity and assists in pore formation, and can form closed pores or micropores or mesopores with extremely small openings inside the amorphous carbon material, which is beneficial to the storage of sodium ions on the low potential platform and increases the proportion of platform capacity. In addition, the present application cooperates to increase the interplanar spacing d of the amorphous carbon material. 002, which can enhance the electron conduction effect and improve the sodium storage performance of the amorphous carbon material. At the same time, the values of La and Lc of the amorphous carbon material are controlled to be relatively small, the disorder of the corresponding material is increased, and the degree of defects is larger, which can provide more sodium ion storage sites, which is conducive to the rapid transmission and release of charges. Combined with the more closed pores or small open pores in the above-mentioned materials, it can reduce the contact and side reactions between the material and the electrolyte, and improve the first coulombic efficiency and cycle performance of the sodium ion battery.
[0006] In some embodiments, the amorphous carbon material satisfies at least one of the following conditions:
[0007] (1) Interplanar spacing d of amorphous carbon materials 002 0.368nm to 0.395nm;
[0008] (2) La of amorphous carbon materials is 7.9nm to 10.5nm;
[0009] (3) The Lc of the amorphous carbon material is 1.1 nm to 2.1 nm. When the microstructure of the amorphous carbon material is regulated to meet the above conditions, it can better cooperate with the cross-linked structure in the material to improve the first coulombic efficiency and cycle performance of the sodium ion battery. In particular, when the amorphous carbon material satisfies the above conditions (1) to (3) at the same time, the resulting sodium ion battery can exhibit better first coulombic efficiency and cycle performance.
[0010] In some embodiments, based on the mass of the amorphous carbon material, the mass percentage of the M element is 1.1% to 5.0%. Controlling the mass percentage of the M element in the amorphous carbon material to satisfy the above relationship can form suitable closed pores through cross-linking, further improving the first coulombic efficiency and cycle performance of the sodium ion battery.
[0011] In some embodiments, in the C1s spectrum of the amorphous carbon material, based on the total mass of the amorphous carbon material, CM X The mass percentage of -C covalent bonds is 41% to 49%, and the mass percentage of C-MO X The mass percentage of C-C covalent bonds is 39% to 51%. X -C covalent bond and C-MO X When the content of -C covalent bonds satisfies the above relationship, the first coulombic efficiency and cycle performance of sodium ion batteries can be further improved.
[0012] In the second aspect, the present application provides a method for preparing any one of the above-mentioned amorphous carbon materials, comprising the following steps: Step 1, mixing asphalt and M element to obtain a mixture, placing the mixture in an inert atmosphere, and then heating the mixture to a pretreatment temperature and performing pretreatment to obtain an intermediate; the heating rate to the pretreatment temperature is 0.2℃ / min to 30℃ / min; the pretreatment temperature is 80℃ to 600℃; the pretreatment time is 0.5h to 10h; Step 2, placing the intermediate in an inert atmosphere, and then heating the mixture to a carbonization temperature and performing carbonization treatment to obtain an amorphous carbon material; the heating rate to the carbonization temperature is 0.2℃ / min to 30℃ / min; the carbonization temperature is 800℃ to 2000℃; the carbonization treatment time is 0.5h to 10h. This preparation method uses asphalt as a carbon source and mixes it with M element to form a precursor material which is subjected to pretreatment and high-temperature carbonization treatment. Compared with the existing technology, it can obtain amorphous carbon materials with high platform characteristics at a relatively low temperature. This preparation method has the advantages of strong operability, high carbon yield, simple raw materials, high consistency in the morphology of the prepared product, high safety and high reaction efficiency.
[0013] In some embodiments, the mass ratio of asphalt to M element is 1:(0.3-3.0); and / or, M element is selected from at least one of sulfur element, selenium element or tellurium element.
[0014] In some embodiments, the inert atmosphere includes nitrogen and / or argon.
[0015] Preferably, the inert atmosphere further comprises hydrogen, and the volume proportion of the hydrogen is 5% to 40% based on the volume of the inert gas.
[0016] In a third aspect, the present application provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises any one of the above-mentioned amorphous carbon materials or an amorphous carbon material obtained by any one of the preparation methods.
[0017] In some embodiments, the negative electrode plate and the sodium metal plate are prepared into a button battery, which is charged at a constant current of 0.1C to a cut-off voltage of 2.5V. Based on the total capacity of the button battery, the capacity with a charging potential below 0.1V accounts for 61% to 74%.
[0018] In a fourth aspect, the present application provides a sodium ion battery comprising any one of the above-mentioned negative electrode plates.
[0019] The beneficial effects of the present application are as follows: the present application discloses an amorphous carbon material and a preparation method thereof, which can achieve the following effects through pretreatment and carbonization of M element: (1) M element can react with asphalt carbon source under pretreatment conditions to form CM X-C covalent bond, C-MO X -C covalent bond, preventing the orderly stacking of carbon layers in the subsequent high-temperature carbonization process, thereby inhibiting the graphitization of carbon materials at high temperatures; (2) M atoms in amorphous carbon materials can change the electron distribution in the carbon layer, inducing the formation of curled carbon layers during the carbonization process, which is conducive to the formation of closed pores, thereby achieving high platform capacity; (3) Compared with oxygen atoms or nitrogen atoms, M atoms including at least one of S atoms, Se atoms or Te atoms are easier to remove at a lower temperature, so that the temperature for constructing high platform characteristic asphalt-based carbon materials is significantly reduced. Based on this, the method provided in this application can obtain amorphous carbon materials with high platform characteristics and high capacity at relatively low temperatures such as 800°C or 1300°C, and the reversible specific capacity at 0.1C can be as high as 315mAh / g or more, and the platform capacity accounts for more than 60%. After 100 cycles at 0.5C, the reversible specific capacity can be maintained at more than 205mAh / g, with excellent electrochemical performance and huge potential commercial value, which is suitable for promotion and application.
[0020] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present application in conjunction with the accompanying drawings. The specific implementation methods of the present application are given in detail by the following embodiments and their accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the implementation methods of the present application, the drawings required for use in the implementation methods will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 is the first cycle charge and discharge curve of the amorphous carbon material (A3) prepared in Example 3 of the present application under 0.1C conditions;
[0023] Figure 2 1 is a cycle performance diagram of the amorphous carbon material of Example 3 and Comparative Example 1 of the present application;
[0024] Figure 3 is the S2p XPS graph of the amorphous carbon materials of Examples 2, 3 and 4 of the present application;
[0025] Figure 4 is the first cycle charge and discharge curve of the amorphous carbon material (A6) prepared in Example 6 of the present application under 0.1C conditions;
[0026] Figure 5is the XRD pattern of the amorphous carbon material (A6) prepared in Example 6 of the present application;
[0027] Figure 6 is the first cycle charge and discharge curve of the amorphous carbon material (A9) prepared in Example 9 of the present application under 0.1C conditions;
[0028] Figure 7 is a SEM image of the amorphous carbon material (A9) prepared in Example 9 of the present application;
[0029] Figure 8 It is the first cycle charge and discharge curve of the amorphous carbon material (B1) prepared in Comparative Example 1 of the present application under 0.1C conditions;
[0030] Fig. 9 is the XRD pattern of the amorphous carbon material (B1) prepared in Comparative Example 1 of the present application;
[0031] Fig.10 is a SEM image of the amorphous carbon material (B1) prepared in Comparative Example 1 of the present application;
[0032] Fig.11 Small-angle X-ray scattering diagrams of the amorphous carbon materials of Examples 2 to 4 and Comparative Example 1 of the present application;
[0033] Fig.12 The amorphous carbon material of Examples 2 to 4 and Comparative Example 1 of the present application is SAXS intensity and N 2 Pore volume fraction plot from adsorption / desorption. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0035] Mechanistic studies on the electrochemical curves of amorphous carbon materials show that the platform segment originates from the filling of sodium ions in closed pores, while the slope segment is related to the defects and functional groups of carbon materials. Closed pores are formed by the stacking and winding of graphite microcrystalline domains composed of carbon layers of a certain size, which is closely related to the precursor and carbonization temperature of the carbon material. Therefore, the selection of a suitable precursor or the corresponding precursor treatment process is a key. However, for a certain precursor, the content of closed pores usually increases first and then decreases with the increase of temperature, and the content of closed pores reaches a maximum between 1500℃ and 1900℃. In this temperature range, the content of defects and functional groups of carbon materials decreases sharply, and the reversible capacity provided by them is significantly reduced. Therefore, the high platform characteristics of amorphous carbon materials can usually be achieved above 1500℃. Therefore, the preparation of carbon materials with high platform characteristics or high platform characteristics at a relatively reduced temperature has great research significance and industrial application prospects.
[0036] As a petrochemical byproduct, asphalt has low cost and high carbon content, and is considered to be a promising carbon material precursor. However, due to its soft carbon precursor properties, direct high-temperature carbonization and pyrolysis of asphalt often results in a soft carbon material with a high degree of graphitization. There are almost no closed pores inside the material, so the sodium storage performance is poor (<100mAh·g -1 ), which is difficult to meet the commercial application of sodium ion batteries. Therefore, it is a key technology that needs to be developed urgently to develop new microstructure control methods for low-cost asphalt precursors to obtain a large number of closed pores and extremely low defect content at a lower temperature, thereby realizing asphalt-based carbon materials with high platform capacity.
[0037] Based on the above problems, the present application proposes an amorphous carbon material, including an M element, wherein the M element is selected from at least one of sulfur, selenium or tellurium; the amorphous carbon material contains CM X -C covalent bond and C-MO X -C covalent bond, wherein x is selected from 1 or 2; the interplanar spacing d of the amorphous carbon material 002is 0.355nm to 0.410nm; La of the amorphous carbon material is 6.2nm to 11.0nm; Lc of the amorphous carbon material is 1.1nm to 4.2nm. The present application uses M element to chemically crosslink the amorphous carbon. The chemical crosslinking includes CC of the amorphous carbon material and chemical bonds with S, Se or Te respectively, which react chemically at high temperature to form covalent bonds; these formed covalent bonds make it difficult to break and arrange neatly during the high-temperature carbonization process, thereby forming a turbulent carbon layer that is more conducive to the diffusion and storage of sodium ions, which is beneficial to improving the overall reversible specific capacity of sodium ions, and assisting pore formation (the pore formation effect comes from the turbulent carbon layers caused by chemical crosslinking, which are intertwined to form sub-nanometer closed pores, and from the formation of a three-dimensional network structure. Some ions are bound by the carbon layer, so that a small amount of ions can only be removed at a higher temperature. The higher removal temperature is conducive to destroying some carbon layers that have been neatly arranged at low temperature, and forming micropores and mesopores with extremely small openings; both pore structures are conducive to the storage of sodium ions on the low potential platform, which is beneficial to increasing the platform capacity share). The multi-closed pore framework structure formed by the above-mentioned chemical cross-linking, combined with the larger interlayer spacing of the amorphous carbon material and the increase in the disorder and chaos of the material, can further improve the sodium storage capacity and sodium ion dynamics of the amorphous carbon material, and improve the first coulombic efficiency and cycle performance of the sodium ion battery.
[0038] For example, the interplanar spacing d of the shaped carbon material is 002The La of the amorphous carbon material is 6.2 nm to 11.0 nm, for example, 6.2 nm, 6.3 nm, 6.6 nm, 7.0 nm, 7.6 nm, 7.7 nm, 7.8 nm, 7.9 nm, 8.1 nm, 8.2 nm, 8.3 nm, 8.4 nm, 8.6 nm, 8.7 nm, 8.8 nm, 8.9 nm, 9.0 nm, 9.1 nm, 9.2 nm, 9.3 nm, 9.4 nm, 9.5 nm, 9.6 nm, 9.7 nm, 9.8 nm, 9.9 nm, 9.9 nm, 9.1 nm, 9.2 nm, 9.3 nm, 9.4 nm, 9.5 nm, 9.6 nm, 9.7 nm, 9.8 nm, 9.9 nm, 9.9 nm, 9.1 nm, 9.2 nm, 9.3 nm, 9.4 nm, 9.5 nm, 9.6 nm, 9.7 nm, 9.8 nm, 9.9 nm, 9.9 nm, 9. The Lc of the amorphous carbon material is 1.1 nm to 4.2 nm, for example, it can be 1.1 nm, 1.2 nm, 1.4 nm, 1.6 nm, 2.0 nm, 2.3 nm, 2.3 nm, 2.8 nm, 3.0 nm, 3.1 nm, 3.4 nm, 3.7 nm, 3.8 nm, 4.1 nm, 4.2 nm or a value within the range of any two thereof. When the interlayer spacing and disorder of the amorphous carbon material are regulated to meet the above conditions, it can better cooperate with the cross-linked structure in the material to improve the first coulombic efficiency and cycle performance of the sodium ion battery.
[0039] In some embodiments, based on the mass of the amorphous carbon material, the mass percentage of the M element is 1.1% to 5.0%, for example, it can be 1.1%, 1.3%, 1.6%, 1.9%, 2.0%, 2.5%, 2.9%, 3.2%, 3.3%, 3.6%, 3.9%, 4.1%, 4.6%, 4.9%, 5.0% or a value in the range of any two thereof. Controlling the mass percentage of the M element in the amorphous carbon material to satisfy the above relationship can form suitable closed pores through cross-linking, increase the closed pore ratio, and further improve the first coulombic efficiency and cycle performance of the sodium ion battery.
[0040] In some embodiments, in the C1s spectrum of the amorphous carbon material, based on the total mass of the amorphous carbon material, CM X The mass percentage of C-MO covalent bonds is 41% to 49%, for example, 41.00%, 41.07%, 42.18%, 42.83%, 43.25%, 43.52%, 44.49%, 45.26%, 45.79%, 46.48%, 46.87%, 47.16%, 48.28%, 48.61%, 49.00% or a value within the range of any two thereof; XThe mass percentage of -C covalent bonds is 39% to 51%, for example, 39.00%, 39.58%, 40.14%, 41.62%, 42.67%, 42.77%, 44.05%, 44.65%, 45.95%, 47.25%, 47.76%, 48.80%, 49.84%, 50.69%, 51.00% or a value within the range of any two thereof. X -C covalent bond and C-MO X When the mass percentage of -C covalent bonds satisfies the above relationship, it can further optimize the cross-linking structure inside the amorphous carbon material, increase the proportion of closed pores, increase the capacity proportion of the low potential platform in the sodium ion battery charge and discharge curve, and improve the first coulombic efficiency and cycle performance.
[0041] In some embodiments, the amorphous carbon material also includes a C=S covalent bond. In the C1s spectrum of the amorphous carbon material, based on the total mass of the amorphous carbon material, the mass percentage of the C=S covalent bond is 0.7% to 1.5%, for example, it can be 0.70%, 0.73%, 0.77%, 0.87%, 0.89%, 0.95%, 1.06%, 1.07%, 1.17%, 1.20%, 1.29%, 1.35%, 1.40%, 1.44%, 1.5% or a value within the range of any two of them.
[0042] In some embodiments, the amorphous carbon material of the present application is subjected to small angle X-ray scattering analysis (SAXS), and the amorphous carbon material is From the SAXS intensity at , it can be seen that based on the total pore volume of amorphous carbon, the pore volume of closed pores accounts for 97.0% to 98.5%, for example, it can be 97.0%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, 97.7%, 97.9%, 98.0%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5% or a value in the range composed of any two of them.
[0043] In the present application, the preparation method of the above-mentioned amorphous carbon material includes the following steps: Step 1, mix asphalt and M element to obtain a mixture, place the mixture in an inert atmosphere, and then heat it to a pretreatment temperature and perform pretreatment to obtain an intermediate; the heating rate for heating to the pretreatment temperature is 0.2℃ / min to 30℃ / min; the pretreatment temperature is 80℃ to 600℃; the pretreatment time is 0.5h to 10h; Step 2, place the intermediate in an inert atmosphere, and then heat it to a carbonization temperature and perform carbonization treatment to obtain an amorphous carbon material; the heating rate for heating to the carbonization temperature is 0.2℃ / min to 30℃ / min; the carbonization temperature is 800℃ to 2000℃; the carbonization treatment time is 0.5h to 10h. The present application promotes the chemical cross-linking of the asphalt carbon source and the M element through pretreatment and carbonization treatment through the above-mentioned preparation method to form CM X -C covalent bond and C-MO X -C covalent bonds can form turbulent carbon layers that are more conducive to the diffusion and storage of sodium ions, as well as closed pores, micropores or mesopores with extremely small openings, which is beneficial to increasing the platform capacity share of sodium ion batteries, and can also increase the interlayer spacing and disorder of amorphous carbon materials. In combination with closed pores, it can further improve the first coulombic efficiency and cycle performance of sodium ion batteries.
[0044] In some embodiments, the asphalt is selected from at least one of low-temperature coal asphalt, medium-temperature coal asphalt, high-temperature coal asphalt, petroleum asphalt and coal tar asphalt. In the present application, low-temperature coal asphalt refers to coal asphalt with a softening point of ≤75°C; medium-temperature coal asphalt refers to coal asphalt with a softening point of >75°C and ≤95°C; high-temperature coal asphalt refers to coal asphalt with a softening point of >95°C.
[0045] In some embodiments, the mass ratio of asphalt and M is 1:(0.3-3.0), for example, the mass ratio of asphalt and M is 1:0.3, 1:0.5, 1:0.7, 1:0.9, 1:1.2, 1:1.4, 1:1.5, 1:1.8, 1:2.2, 1:2.3, 1:2.5, 1:2.6, 1:2.8, 1:3 or a value within the range of any two thereof. When the mass ratio of asphalt and M is regulated to meet the above range, it is beneficial to enhance the chemical crosslinking effect, increase the closed-cell ratio of amorphous carbon materials, and further improve the first coulombic efficiency and cycle performance of sodium ion batteries. Preferably, the mass ratio of asphalt and M is 1:(0.5-1.5), and more preferably 1:(0.7-1.2).
[0046] In some embodiments, the specific method for obtaining the mixture is: asphalt and sulfur / selenium are mixed after being treated by any one of wet mixing and solid phase grinding, and then dried by any one of freezing, vacuum or heating to obtain the mixture; wherein the solvent for wet mixing is any one of water, nitric acid, ethanol, acetone, cyclohexane, carbon disulfide, benzene, toluene, and quinoline.
[0047] In some embodiments, the inert atmosphere includes nitrogen and / or argon, and the inert atmosphere further includes hydrogen, and the volume proportion of hydrogen is 5% to 40% based on the volume of the inert gas, for example, 5%, 7%, 9%, 12%, 15%, 18%, 19%, 24%, 26%, 29%, 31%, 33%, 36%, 40% or a value in the range of any two thereof. For example, the inert atmosphere is a mixed gas formed by argon and hydrogen.
[0048] In some embodiments, the heating rate to the pretreatment temperature is 0.2°C / min to 30°C / min, for example, 0.2°C / min, 1.8°C / min, 4.2°C / min, 5.4°C / min, 8.3°C / min, 9.9°C / min, 13.9°C / min, 15.8°C / min, 17.8°C / min, 20.0°C / min, 21.0°C / min, 25.3°C / min, 25.9°C / min, 28.4°C / min, 30°C / min or a value within the range of any two thereof; the pretreatment temperature is 80 ℃ to 600℃, for example, 80℃, 94℃, 158℃, 172℃, 208℃, 258℃, 315℃, 353℃, 388℃, 420℃, 447℃, 519℃, 541℃, 565℃, 600℃ or a value within the range of any two thereof; the pretreatment time is 0.5h to 10h, for example, 0.5h, 0.6h, 1.3h, 2.6h, 3.2h, 4.2h, 4.7h, 5.2h, 6.2h, 6.7h, 7.7h, 7.9h, 9.1h, 9.4h, 10h or a value within the range of any two thereof. When the pretreatment conditions are regulated to meet the above range, it is beneficial to improve the chemical crosslinking effect of the asphalt carbon source and the M element, improve the closed pore ratio, interlayer spacing and disorder of the amorphous carbon material, and improve the first coulombic efficiency and cycle performance of the sodium ion battery.
[0049] In some embodiments, the heating rate to the carbonization temperature is 0.2°C / min to 30°C / min, for example, 0.2°C / min, 1.8°C / min, 4.2°C / min, 5.4°C / min, 8.3°C / min, 9.9°C / min, 13.9°C / min, 15.8°C / min, 17.8°C / min, 20.0°C / min, 21.0°C / min, 25.3°C / min, 25.9°C / min, 28.4°C / min, 30°C / min or a value in the range of any two thereof; the carbonization temperature is 800°C to 2000°C, For example, it is 800°C, 850°C, 980°C, 1050°C, 1140°C, 1230°C, 1280°C, 1440°C, 1520°C, 1620°C, 1660°C, 1740°C, 1850°C, 1960°C, 2000°C or a value within the range consisting of any two of them; the carbonization treatment time is 0.5h to 10h, for example, 0.5h, 0.6h, 1.3h, 2.6h, 3.2h, 4.2h, 4.7h, 5.2h, 6.2h, 6.7h, 7.7h, 7.9h, 9.1h, 9.4h, 10h or a value within the range consisting of any two of them. When the conditions of the carbonization treatment are regulated to meet the above range, it is beneficial to improve the chemical cross-linking effect of the asphalt carbon source and the M element, increase the closed-pore ratio, interlayer spacing and disorder of the amorphous carbon material, and further improve the first coulombic efficiency and cycle performance of the sodium ion battery.
[0050] In the present application, a negative electrode plate is also provided, comprising a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises any one of the above-mentioned amorphous carbon materials or an amorphous carbon material obtained by any one of the preparation methods.
[0051] In some embodiments, the negative electrode plate and the sodium metal plate are prepared into a button battery, and a constant current is charged at a current of 0.1C to a cut-off voltage of 2.5V. Based on the total capacity of the button battery, the capacity with a charging potential below 0.1V accounts for 61% to 74%. In other words, the platform potential of the amorphous carbon material of the present application is 61% to 74%, for example, it can be 61.0%, 61.5%, 62.8%, 63.3%, 64.8%, 65.4%, 66.9%, 67.1%, 68.1%, 69.8%, 70.6%, 71.5%, 72.4%, 73.2%, 74.0% or a value within the range composed of any two of them. The amorphous carbon material of the present application forms closed pores through chemical cross-linking of the M element, and cooperates with the interplanar spacing d 002 And the regulation of disorder can increase the capacity of the platform segment, which is beneficial to improving the first coulombic efficiency and cycle performance of sodium-ion batteries.
[0052] In some embodiments, the negative electrode current collector includes at least one of aluminum foil, copper foil or stainless steel foil. In the present application, the negative electrode active material layer also includes a binder, and the binder includes at least one of sodium cellulose, sodium carboxymethyl cellulose, hydroxypropyl cellulose, sodium hydroxymethyl cellulose, potassium hydroxymethyl cellulose, diacetyl cellulose, polyacrylic acid, sodium alginate, styrene-butadiene rubber, acrylic butadiene rubber, polypyrrole, polyaniline, epoxy resin or guardo gum.
[0053] In some embodiments, the preparation method of the above-mentioned negative electrode plate includes the following steps: adding the above-mentioned artificial SEI film-modified amorphous carbon material and polymer binder to a solvent and stirring them into a uniform slurry, coating the slurry on the negative electrode collector, and drying to obtain the negative electrode; wherein the solvent can be selected from at least one of water, acetone, N-methylpyrrolidone, dimethylformamide or ethanol.
[0054] Finally, the present application provides a sodium ion battery comprising any one of the above-mentioned negative electrode plates.
[0055] In the present application, the sodium ion battery also includes a positive electrode, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material may include at least one of a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries can also be used.
[0056] In some embodiments, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr or Ce. The sodium transition metal oxide is, for example, Na x MO 2 , wherein M is at least one of Ti, V, Mn, Co, Ni, Fe, Cr or Cu, and 0<x≤1.
[0057] In some embodiments, the polyanionic compound may be a compound having sodium ions, transition metal ions and tetrahedral (YO 4 ) n A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr or Ce; Y can be at least one of P, S or Si; n represents (YO 4 ) n valence state.
[0058] The polyanionic compound can also be a compound having sodium ions, transition metal ions, tetrahedral (YO 4 ) nA class of compounds containing anion units and halogen anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr or Ce; Y can be at least one of P, S or Si, and n represents (YO 4 ) n valence state; the halogen may be at least one of F, Cl or Br.
[0059] The polyanionic compound can also be a compound having sodium ions, tetrahedral (YO 4 ) n Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S or Si, and n represents (YO 4 ) n valence state; Z represents a transition metal, which may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr or Ce; m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl or Br.
[0060] Polyanionic compounds are, for example, NaFePO 4 、Na 3 V 2 (PO 4 ) 3 、NaM'PO 4 F (M' is one or more of V, Fe, Mn and Ni) or Na 3 (VO y ) 2 (PO 4 ) 2 F 32y At least one of (0≤y≤1).
[0061] The Prussian blue compound may be a compound having sodium ions, transition metal ions and cyanide ions (CN). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. a Me b Me' c (CN) 6 , wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co or Zn, 0<a≤2, 0<b<1, 0<c<1.
[0062] In some embodiments, the positive electrode active material layer may further include a conductive agent to improve the conductivity of the positive electrode. The present application does not specifically limit the type of the conductive agent, and may be selected according to actual needs. As an example, the conductive agent may be at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, or carbon nanofibers.
[0063] In some embodiments, the positive electrode active material layer may further include a binder to firmly bond the positive electrode active material and the optional conductive agent to the positive electrode current collector. The present application does not specifically limit the type of binder and can be selected according to actual needs. As an example, the binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene vinyl acetate copolymer (EVA), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA) or carboxymethyl chitosan (CMCS).
[0064] In some embodiments, the positive electrode current collector may be a conductive carbon sheet, a metal foil, a carbon-coated metal foil, a porous metal plate or a composite current collector, wherein the conductive carbon material of the conductive carbon sheet may be at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene or carbon nanofibers, and the metal material of the metal foil, the carbon-coated metal foil and the porous metal plate may be independently selected from at least one of copper, aluminum, nickel or stainless steel. The composite current collector may be a composite current collector formed by a metal foil and a polymer base film.
[0065] The positive electrode current collector is, for example, one or more of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh and carbon-coated aluminum foil, preferably aluminum foil.
[0066] The positive electrode can be prepared according to conventional methods in the art. Usually, the positive electrode active material and optional conductive agent and binder are dispersed in a solvent (such as N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry, which is then coated on the positive electrode current collector, and then dried and cold pressed to obtain the positive electrode.
[0067] The sodium ion battery of the present application also includes an isolation membrane, which can be any material suitable for an isolation membrane of an electrochemical energy storage device in the art, for example, it can be at least one of but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester or natural fiber.
[0068] The electrolyte may include an organic solvent and an electrolyte sodium salt. As an example, the organic solvent may also include at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, fluoroethylene carbonate, ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, or methyl tert-butyl ether; the electrolyte sodium salt may be at least one of sodium hexafluorophosphate, sodium bis(trifluoromethanesulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, or sodium chloride.
[0069] The positive electrode, the separator, and the negative electrode are stacked in order, so that the separator is between the positive electrode and the negative electrode to play an isolating role, to obtain a battery cell, or the battery cell can be obtained after winding; the battery cell is placed in a packaging shell (which can be a soft package, a square aluminum shell, a square steel shell, a cylindrical aluminum shell and a cylindrical steel shell), an electrolyte is injected and sealed to obtain a sodium ion battery.
[0070] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application. Unless otherwise specified, the raw materials used in the following embodiments are all from ordinary commercial products, and the devices or equipment used are all purchased from conventional market sales channels.
[0071] Example 1
[0072] The amorphous carbon material of this embodiment is prepared by a method comprising the following steps:
[0073] Step 1, grinding: taking asphalt and sublimed sulfur in a mass ratio of 1:0.5, mixing them at a grinding speed of 500 r / min for 1 h to obtain a mixture;
[0074] Drying: The ground mixture was placed in an oven at 100°C and dried for 12 h;
[0075] Pretreatment: The dried mixture is placed in a tube furnace for pretreatment. During the pretreatment, a sulfurization reaction occurs. Argon is used as the sulfurization atmosphere. The temperature of the pretreatment tube furnace is set as follows: when the furnace temperature is less than 150°C, the temperature is increased at a rate of 0.2°C / min. When the furnace temperature is ≥150°C, the temperature is kept for 0.5h. Then the pretreated intermediate material is allowed to cool naturally to room temperature.
[0076] Step 2, carbonization treatment: grind the intermediate material obtained after pretreatment and place it in a high-temperature tube furnace for carbonization treatment, and during the carbonization process, argon is used as the carbonization atmosphere. The temperature of the high-temperature tube furnace is set as follows: when the furnace temperature is less than 1100°C, increase the temperature at a rate of 0.5°C / min, and when the furnace temperature is ≥1100°C, keep warm for 3 hours. Carbonization treatment obtains the amorphous carbon material in this embodiment, and then the amorphous carbon material is naturally cooled to room temperature.
[0077] Sorting: The amorphous carbon material obtained after carbonization treatment is passed through a 200-mesh vibrating screen and a sorting device to obtain an amorphous carbon material with a uniform particle size (the amorphous carbon material is numbered A1).
[0078] Embodiments 2 to 10
[0079] The preparation methods of the amorphous carbon materials provided in Examples 2 to 10 are basically the same as those in Example 1, with the main differences being the process parameter settings, component ratios and M element, as shown in Table 1, wherein elemental S, Se and Te are respectively sublimated sulfur, selenium powder and tellurium powder, and the drying of Examples 7, 8 to 10 is freeze-drying, with a freeze-drying time of 12 hours. The samples obtained in Examples 2 to 10 are A2 to A10, respectively.
[0080] Comparative Example 1
[0081] The preparation method of the amorphous carbon material in this comparative example is basically the same as the method steps of Example 1, with the main difference being that no sublimated sulfur is added, and in step 1 only asphalt is ground, followed by subsequent drying, pretreatment, carbonization treatment and sorting. The obtained amorphous carbon material is numbered B1.
[0082] Comparative Examples 2 to 4
[0083] The preparation methods of the amorphous carbon materials provided in Comparative Examples 2 to 4 are basically the same as the method steps of Comparative Example 1, and the main differences are the process parameter settings, component ratios and M single substances, as shown in Table 1, wherein the drying of Comparative Examples 3 and 4 adopts freeze drying, and the freeze drying time is 12h. The samples obtained in Comparative Examples 2 to 4 are B2 to B4 respectively.
[0084] Table 1
[0085]
[0086]
[0087] Performance Test:
[0088] The amorphous carbon materials A1-A10 and B1-B4 prepared in the above-mentioned examples 1-10 and comparative examples 1-4 were respectively used as active materials, assembled into sodium ion batteries according to the following method, and the following electrochemical performance tests were performed. The test results are shown in Table 2. The preparation method of the sodium ion battery comprises the following steps:
[0089] (1) The above active materials were mixed and ground with sodium alginate in a mass ratio of 9:1, and deionized water was added for wet grinding until the slurry could pass through a 200-mesh stainless steel sieve;
[0090] (2) using a wet film applicator to apply the slurry ground in step (1) onto copper foil to a thickness of 200 μm, and then transferring to a vacuum oven at 120° C. and drying for 12 h to obtain an electrode;
[0091] (3) The electrode piece in step (2) was cut into small discs with a diameter of 12 mm and transferred to a glove box filled with argon. The button cell was assembled in the order of negative electrode shell, spring sheet, gasket, metal sodium sheet, diaphragm, small disc electrode piece, and positive electrode shell, and 150 μL of electrolyte was added (the button cell model used was CR2032, the diaphragm was a glass fiber diaphragm, and the electrolyte was sodium hexafluorophosphate (NaPF 6 ) is dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate (mass ratio is 1:1), wherein, based on the mass of the electrolyte, NaPF 6 After the assembly is completed, the sodium ion battery is obtained after standing at room temperature for 8 hours.
[0092] Discharge specific capacity and charge specific capacity test: The sodium ion battery is discharged at a constant current of 0.1C to a cut-off voltage of 0V, and the discharge specific capacity of the sodium ion battery is measured; the sodium ion battery is charged at a constant current of 0.1C to a cut-off voltage of 2.5V, and the charge specific capacity of the sodium ion battery is measured.
[0093] First coulombic efficiency = charge specific capacity / discharge specific capacity × 100%.
[0094] Draw the charge and discharge curve of the sodium ion battery. Based on the charging curve, calculate the capacity ratio of the sodium ion battery with a charging potential below 0.1V compared to the total capacity of the sodium ion battery, which is the platform ratio of the sodium ion battery.
[0095] Table 2
[0096]
[0097]
[0098] Figure 1 , Figure 4 , Figure 6 and Figure 8 The first cycle charge and discharge curves of A3, A6, A9 and B1 under 0.1C conditions. Figure 1 , Figure 4 , Figure 6 and Figure 8 It can be seen from the comparison that the amorphous carbon material prepared by the method of Example 3 in the present application has a discharge capacity (i.e., discharge specific capacity, Capacity) of up to 448 mAh / g, a reversible capacity (i.e., charging capacity, charging specific capacity, Capacity) of up to 315.2 mAh / g, and a coulombic efficiency of 70.36% during the first charge and discharge process; the amorphous carbon material prepared by the method of Example 6 has a discharge capacity of up to 416.64 mAh / g, a reversible capacity of up to 330.30 mAh / g, and a coulombic efficiency of 79.27% during the first charge and discharge process; the amorphous carbon material prepared by the method of Example 9 has a discharge capacity of up to 379.70 mAh / g, a reversible capacity of up to 317.60 mAh / g, and a coulombic efficiency of 83.64% during the first charge and discharge process; and the amorphous carbon material prepared by the method of Comparative Example 1 has a discharge capacity of 153.60 mAh / g, a reversible capacity of 109 mAh / g, and a coulombic efficiency of 70.96% during the first charge and discharge process. The amorphous carbon materials prepared by the preparation methods in Examples 1 to 10 and Comparative Examples 1 to 4 were charged and discharged for the first time, and their discharge capacity, reversible capacity and coulombic efficiency are shown in Table 2. It was found that the platform proportion of Examples 1 to 10 exceeded 60%, and the total reversible specific capacity exceeded 300 mAh / g. It can be shown that the amorphous carbon material prepared by the preparation method of the present application has a great improvement in discharge capacity, reversible capacity and coulombic efficiency, indicating that the preparation method provided by the present application method and the amorphous carbon material obtained can effectively improve the sodium storage performance.
[0099] X-ray photoelectron spectroscopy analysis (XPS analysis) was performed on the amorphous carbon materials of Examples 2, 3 and 4 of the present application and Comparative Example 1 to analyze the chemical bond state of the organic matter. Figure 3 : This is the S2p XPS graph of the amorphous carbon materials of Examples 2, 3 and 4 of the present application. The platform ratios, the mass percentages of each chemical bond in the C 1s spectrum and the mass percentages of each chemical bond in the S2p spectrum of the amorphous carbon materials of the above examples and comparative example 2 were tested, and the results are shown in Table 3 below.
[0100] Table 3
[0101]
[0102] Depend on Figure 3 As shown in Table 3, the amorphous carbon materials prepared in Examples 2 to 4 of the present application all contain CS X -C bond, C=S bond and C-SOX -C chemical bonds, and the changes of these chemical bonds are shown in Table 3. With the increase of the S content in the bulk phase, the platform capacity of the amorphous carbon materials prepared in Examples 2 to 4 and Comparative Example 2, as compared with those prepared in Comparative Example 2, and the partial covalent bond content calculated by XPS C 1s and S2p spectra are all increased, and by comparing the component ratios of Examples 2 to 4, it is found that the higher the mass ratio of sublimated sulfur to asphalt, the higher the S content in the bulk phase of the sample, and whether it is C 1s or S2p X -C, C-SO X -C and C=S will increase with the increase of the mass ratio of sublimated sulfur to asphalt. The platform capacity ratio will increase with the increase of the partial covalent bond content calculated by XPS C 1s and S2p spectra, and will not increase significantly after reaching a certain level. This shows that the platform ratio and CS X -C, C-SO X -C and C=S chemical bonds are positively correlated, and the increase slows down after reaching a certain level.
[0103] Cycle performance test: The sodium ion battery is discharged at a constant current of 0.5C to 0V, and then charged at a constant current of 0.5C with a cut-off voltage of 2.5V. This process is regarded as one cycle. After 160 cycles, the discharge specific capacity of the sodium ion battery is measured.
[0104] Figure 2 : is a cycle performance diagram of the amorphous carbon material of Example 3 and Comparative Example 1 of the present application. Figure 2 As shown, the amorphous carbon material of comparative example 1 has a discharge specific capacity of 111 mAh / g after 160 cycles. Compared with Example 2, the comparative example is not cross-linked and modified by sulfur element, and the discharge specific capacity of the battery is significantly reduced. The reason is that after sulfur cross-linking modification in Example 3 of the present application, the carbon material has a multi-closed pore framework structure and a larger interlayer spacing, and the material disorder and chaos increase; at the same time, the sulfur element is in the form of oxidized sulfur (C-SO X -C) and thiophene sulfur (CSC 2p3 / 2 and CSC 2p1 / 2), which undergo high-temperature pyrolysis to change their microstructure and generate a large number of closed pores, which improve the sodium storage capacity and the kinetics of sodium ions.
[0105] Figure 5 and Fig. 9 The XRD patterns of the amorphous carbon materials prepared in Example 6 and Comparative Example 1 are shown respectively. Figure 5 and Fig. 9 It can be seen from the comparison that the amorphous carbon material prepared by the method of Example 6 in the present application presents a typical bimodal structure of amorphous carbon, corresponding to ( 002 ) and (100) crystal planes, after calculating their d 002 =0.3901, while the d of the amorphous carbon material prepared by the method in Comparative Example 1 is002 is 3.487. Similarly, the amorphous carbon materials prepared by the preparation methods in Examples 1 to 10 and Comparative Examples 1 to 4 are subjected to XRD detection and the interlayer spacing d is calculated. 002 As shown in Table 2, it can be seen that the interlayer spacing d of the amorphous carbon material prepared by the preparation method of the present application is 002 All of them are improved, indicating that the preparation method of M element modification provided by the present application can increase the interlayer spacing and enhance the electronic conduction, thereby improving the sodium storage performance of the amorphous carbon material.
[0106] Figure 7 and Fig.10 The SEM images of the amorphous carbon materials prepared in Example 9 and Comparative Example 1 are shown respectively. Figure 7 and Fig.10 It can be seen that the amorphous carbon material prepared by the preparation method of Example 9 of the present application has a smaller particle size, softened edges, disappeared layered structure, rough surface and formed not very obvious pores. The amorphous carbon material prepared in Comparative Example 1 has sharp edges and large particle morphology, with an obvious layered structure. Similarly, the amorphous carbon materials prepared in Examples 1 to 10 were subjected to SEM testing, and their SEM images were similar to those of the amorphous carbon material in Example 9. This shows that the amorphous carbon material prepared by the method of the present application is beneficial to improving the sodium storage performance of the material.
[0107] In addition, the changes in La and Lc of the amorphous carbon materials prepared by Examples 1 to 10 and Comparative Examples 1 to 4 are shown in Table 2. The amorphous carbon materials prepared in Examples 1 to 10 of the present application have smaller La and Lc than those prepared in Comparative Examples 1 to 4, indicating that the disorder and defect degree of the amorphous carbon materials prepared by the preparation method of the present application are getting bigger and bigger. Moreover, from the first cycle charge and discharge curves of the amorphous carbon materials prepared by Examples 1 to 10 and Comparative Examples 1 to 4 under 0.1C conditions, it can be concluded that their platform share is as shown in Table 2. The platform share of the amorphous carbon material prepared in Comparative Example 1 is 18.10%, while the platform share of the amorphous carbon material prepared in Examples 1 to 10 of the present application is between 63.41% and 71.10%, which shows that its platform share can be further improved.
[0108] Fig.11 The small angle X-ray scattering diagram of the amorphous carbon material of Examples 2 to 4 and Comparative Example 1 of the present application. The amorphous carbon material of Examples 2 to 4 and Comparative Example 1 was subjected to small angle X-ray scattering (SAXS), which is a multi-scale characterization method of pore structure. By fitting the original data, key parameters such as pore distance and fractal dimension can be obtained. According to the SAXS pattern, Fig.11 It can be seen that compared with Comparative Example 1, the A more obvious platform is shown at the point with higher strength, indicating that the amorphous carbon materials of Examples 2 to 4 have more closed pores, and the radius of a large number of closed pores has expanded.
[0109] Fig.12 The amorphous carbon material of Examples 2 to 4 and Comparative Example 1 of the present application is SAXS intensity and N 2 Pore volume percentage diagram obtained by adsorption / desorption. The blue color represents the amorphous carbon material in The SAXS intensity at represents the proportion of closed pore volume in the total pore volume; red represents the pore volume of amorphous carbon materials. Fig.12 It can be seen that the closed-cell ratio increased significantly from 43.3% in Comparative Example 1 to more than 97% in Examples 2 to 4, indicating that M element-induced crosslinking (especially sulfur-induced crosslinking) played a key role in promoting the formation of closed cells. It is worth noting that among these modified carbon materials, Example 3 has the highest closed-cell ratio, reaching 98.5%. This shows that when the mass ratio of asphalt and M element is 1:1, the closed-cell ratio of amorphous carbon materials can be greatly improved, thereby improving the performance of sodium-ion batteries.
[0110] In summary, the present application discloses a method for preparing an amorphous carbon material with high reversible capacity and high platform ratio. The preparation method is to grind, dry and pretreat a precursor material formed by mixing an asphalt carbon source and an M element in different proportions to obtain a precursor material (i.e., an intermediate) formed by mixing an asphalt carbon source and an M element, and then obtain an amorphous carbon material by high-temperature carbonization, cooling, vibrating screen and other treatments. The preparation method has the following advantages: (1) low cost: cheap and readily available raw materials are used, and the experimental process is simple to operate; (2) the materials used are simple to prepare and highly operable: a two-step sintering method is used, which does not require multi-stage heating or other treatments; (3) the preparation process is simple, mainly manifested in the chemical crosslinking of the asphalt carbon source and the M element: chemical crosslinking (chemical crosslinking includes the chemical bonds between the asphalt-based CC and the M element chemically bonding at high temperature to form covalent bonds; these formed covalent bonds make it difficult to break and arrange neatly during the high-temperature carbonization process, thereby forming a turbulent carbon layer that is more conducive to the diffusion and storage of sodium ions, which is beneficial to improving the overall reversible specific capacity of sodium ions) and auxiliary pore formation (pore formation, on the one hand, comes from the turbulent carbon layers caused by chemical crosslinking, which will be interconnected to form sub-nanometer closed pores, and on the other hand, from three The formation of a three-dimensional network structure, some ions are bound by the carbon layer, so that a small amount of ions can only be removed at a higher temperature. The higher removal temperature is conducive to destroying part of the carbon layer that has been neatly arranged at low temperature, and forming extremely small micropores and mesoporous pores; both pore structures are conducive to the storage of sodium ions on the low potential platform, which is conducive to increasing the platform capacity ratio); (4) The prepared product has high morphology consistency: the particle size of the synthesized material is uniform, which solves the problem of poor consistency of the precursor of the negative electrode material of lithium ion battery / sodium ion battery in the past; (5) High safety: The synthesis process does not need to be carried out in a closed manner, thereby avoiding the problem of excessive self-generated pressure during the reaction process, and meeting the green chemistry principle that safety hazards should be minimized in the chemical production process; (6) High reaction efficiency: The reaction is easy to occur, and the preparation of amorphous carbon materials can be completed in a short time. It can be seen that the present application achieves the above effects through simple pretreatment and the effect achieved is obvious. The amorphous carbon material prepared in the present application has multiple closed pores formed by cross-linking of M elements, has high reversible capacity and high platform ratio, and the discharge reversible capacity can be as high as 448 mAh / g at 0.1C. It has excellent sodium storage capacity, huge potential commercial value, and is suitable for promotion and application.
[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present application.
Claims
1. An amorphous carbon material, characterized in that: The amorphous carbon material includes an M element, wherein the M element is selected from at least one of sulfur, selenium or tellurium; the amorphous carbon material contains CM X -C covalent bond and C-MO X -C covalent bond, wherein x is selected from 1 or 2; the interplanar spacing d of the amorphous carbon material 002 0.355nm to 0.410nm; The La of the amorphous carbon material is 6.2nm to 11.0nm; The Lc of the amorphous carbon material is 1.1 nm to 4.2 nm.
2. The amorphous carbon material according to claim 1, characterized in that The amorphous carbon material satisfies at least one of the following conditions: (1) The interplanar spacing d of the amorphous carbon material 002 0.368nm to 0.395nm; (2) The La of the amorphous carbon material is 7.9 nm to 10.5 nm; (3) The Lc of the amorphous carbon material is 1.1 nm to 2.1 nm.
3. The amorphous carbon material according to claim 1 or 2, characterized in that: Based on the mass of the amorphous carbon material, the mass percentage of the M element is 1.1% to 5.0%.
4. The amorphous carbon material according to claim 1 or 2, characterized in that: In the C1s spectrum of the amorphous carbon material, based on the total mass of the amorphous carbon material, the CM X The mass percentage of C-C covalent bonds is 41% to 49%, and the C-MO X The mass percentage of -C covalent bonds is 39% to 51%.
5. The method for preparing an amorphous carbon material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1, mixing asphalt and M element to obtain a mixture, placing the mixture in an inert atmosphere, and then heating it to a pretreatment temperature and pretreating it to obtain an intermediate; the heating rate to the pretreatment temperature is 0.2°C / min to 30°C / min; the pretreatment temperature is 80°C to 600°C; the pretreatment time is 0.5h to 10h; Step 2, placing the intermediate in an inert atmosphere, then heating it to a carbonization temperature and performing a carbonization treatment to obtain the amorphous carbon material; the heating rate to the carbonization temperature is 0.2°C / min to 30°C / min; the carbonization temperature is 800°C to 2000°C; the carbonization treatment time is 0.5h to 10h.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the asphalt to the M element is 1:(0.3-3.0); and / or, The M element is selected from at least one of sulfur, selenium or tellurium.
7. The preparation method according to claim 5, characterized in that: The inert atmosphere includes nitrogen and / or argon; Preferably, the inert atmosphere further comprises hydrogen, and based on the volume of the inert gas, the volume proportion of the hydrogen is 5% to 40%.
8. A negative electrode plate, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the amorphous carbon material according to any one of claims 1 to 4 or the amorphous carbon material obtained by the preparation method according to any one of claims 5 to 7.
9. The negative electrode sheet according to claim 8, characterized in that: The negative electrode plate and the sodium metal plate are prepared into a button battery, which is charged at a constant current of 0.1C to a cut-off voltage of 2.5V. Based on the total capacity of the button battery, the capacity with a charging potential below 0.1V accounts for 61% to 74%.
10. A sodium ion battery, characterized in that: Comprising the negative electrode sheet as described in claim 8 or 9.
Citation Information
Patent Citations
Cathode material for sodium ion battery, and preparation method of cathode material
CN104103835A
Carbon material and preparation method and application thereof
CN113086962A
Amorphous carbon material and preparation method thereof, sodium ion battery negative electrode and sodium ion battery
CN113493193A
Hard carbon material and preparation method thereof, electrochemical device and electronic device
CN115332538A
Preparation method and application of hard carbon material
CN116395667A